Transition of maternal dietary n-3 fatty acids from the yolk to the liver of broiler breeder progeny via the residual yolk sac. (22nd December 2014) - Koppenol, Astrid; Buyse, Johan; Everaert, Nadia; Willems, Els; Wang, Yufeng; Franssens, Lies; Delezie, Evelyne
Abstract : The aim of the present study was to evaluate the transfer of maternal dietary fatty acids (FA) from the yolk to the developing offspring, with special emphasis on n-3 FA eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). Six hundred forty Ross 308 breeders were housed from 6 to 58 wk of age in 16 pens resulting in 4 replicates per dietary treatment. They were fed 1 of 4 diets: a basal diet, rich in n-6 FA (CON), or an n-3 FA enriched diet formulated to obtain an EPA/DHA ratio of 1/1 (EPA = DHA), 1/2 (DHA), or 2/1 (EPA). At 28, 43, and 58 wk of age, 20 eggs per treatment were collected and analyzed for FA composition. At these same breeder ages, 600 fertilized eggs per treatment were incubated. At hatch the residual yolks of 25 chicks per treatment were collected and analyzed for FA composition. At every hatch, 180 chicks per treatment were raised under standard conditions and livers were sampled at d 1, 14, 28, and 38 d for FA analysis. Concentrations of EPA in the yolk and residual yolk of eggs laid by EPA-fed breeders were highest, next-to-highest for EPA = DHA-fed breeders, next-to-lowest for DHA-fed breeders, and lowest in those laid by control hens, reflecting the inclusion levels in the maternal diets. Yolk and residual yolk DHA concentrations, however, were not only elevated due to DHA supplementation, compared with the control diet, but also due to EPA supplementation. Offspring hepatic EPA concentrations were elevated until d 28 in all n-3 enriched groups, whereas hepatic DHA concentrations were only affected by EPA = DHA and DHA supplementation at d 1. No differences were found in hepatic DHA concentrations at later offspring ages. Considering the role of EPA and DHA in early development and growth, the maternal supply of these n-3 FA might improve offspring health and performance.